A critical review of the development and demulsification processes applied for oil recovery from oil in water emulsions - Wamda Faisal (17151025) (2022)
The formation of stable emulsions is a fundamental problem in oil industry that can result in a sequence of environmental and operational problems. Chemical demulsification is extensively applied for the recovery of oil from water as well as water from oil. This review introduces different chemical demulsifiers applied for the demulsification and recovery of oil from oil in water (O/W) emulsions. Main types of surfactants (anionic, cationic, nonionics and amphoteric) involved in the formation of emulsions and enhances their stability were discussed. Promising demulsifiers such as nanoparticle (NP), hyperbranched polymers, and ionic liquids (IL), which achieved high oil recovery rate, parameters influencing demulsification efficiency and demulsification mechanisms were explored. Lastly, improvements, challenges, and new changes being made to chemical demulsifiers were underlined. Functionalized magnetic nanoparticles and hyperbranched polymers were very effective in recovering oil from O/W emulsions with an efficiency >95%. Polymers with highly hydrophilic content and high molecular weight can achieve excellent oil recovery rates due to higher interfacial activity, higher dispersion, and presence of specific functional groups. Although ionic liquids could achieve oil recovery up to 90%, high cost limits their applications. NPs showed excellent oil recovery behavior at low concentrations and ambient temperature. Demulsification efficiency of NPs can be enhanced by functionalize with other components (e.g., polymers and surfactants), while service life can be extend by silica coating. Future challenges include scaling up the use of NPs in oil recovery process and highlighting contrasts between lab-scale and field-scale applications. Other Information Published in: Chemosphere License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.chemosphere.2021.133099